VITAMINS GROUP B, ITS ROLE FOR THE STATE OF HEALTH AND INTELLECTUAL DEVELOPMENT OF CHILDREN - L.V. Levchuk; O.V. Stennikova ("Paediatrician" Publishers LLC, 2009)
This article presents the literature data on physiological role of vitamins group B, prevalence of vitamins of this group deficiency in children, needs of children in vitamins group B, and possible methods of prophylaxis and correction of vitamins deficient states.Key words: children, vitamins group B, deficiency, health.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):42-47)